P172 Changes in pneumococcal serotype distribution of paediatric empyema in the age of pneumococcal conjugate vaccines. (2nd December 2011) - Thomas, M F; Sheppard, C L; Guiver, M; George, R C; Simmister, C; Cliff, D; Gorton, R; Elemraid, M A; Clark, J E; Rushton, S P; Paton, J Y; Spencer, D A
Abstract : Introduction: Pneumococcal infection is the leading cause of paediatric empyema in the UK. The seven valent pneumococcal vaccine (PCV-7) was introduced to the UK routine immunisation schedule in September 2006 and replaced in April 2010 with a 13 valent vaccine (PCV-13). Concerns have been raised in several countries about serotype replacement disease in paediatric empyema following the introduction of PCV-7. We have monitored changes in pneumococcal serotype distribution to determine whether there is evidence of serotype replacement in culture negative paediatric empyema in England following introduction of PCV-7 and PCV-13. Methods: In September 2006, the Health Protection Agency established enhanced surveillance of paediatric culture negative empyema for England in collaboration with members of the British Paediatric Respiratory Society. Samples were forwarded from admitting hospitals, those that were pneumococcal PCR positive underwent non-culture serotyping using a multiplex antigen detection assay capable of detecting 14 serotypes/groups (1, 3, 4, 5, 6A/C, 6B, 7F/A, 8, 9V, 14, 18, 19A, 19F and 23F). Fisher's exact test was used for analysis of count data and incidence rate ratios calculated for individual serotypes. Results: 420 pleural fluid samples from 413 patients were tested. Four serotypes/groups contributed more than 85% of the total serotypes detected (Serotype 1–42.4%, 3–24.3%, 7A/F–10.2% and 19A–8.8%). Changes in individual serotypes and overall counts are shown in Abstract P172 table 1 . PCV-7 serotypes initially contributed 16% of those detected but in 2009/2010 none were detected (p<0.001). There was an increase in the detection of non-PCV-13 serotypes in 2010/2011 although this rise was non-significant (Pre: 1.8%, Post 3.6%, p=0.68). Conclusions: No PCV-7 serotypes were detected in the final year before it was replaced by PCV-13, suggesting that PCV-7 was effective in preventing empyema due to these serotypes. There were significant increases in non-vaccine serotypes/groups, notably 3 and 7A/F, consistent with serotype replacement disease and mirroring changes in invasive pneumococcal disease as a whole. The increase in disease caused by non-PCV-13 serotypes in 2010/2011 highlights the need for ongoing active surveillance. Future changes in serotype distribution are likely, and these may alter the clinical profile of empyema.